Have Non-Native English-Speaking Marine Cadet Engineers Been Educated Appropriately? - Tae-Youl Jeon; Bu-Gi Kim; Nooree Kim; Young-Chan Lee (Journal of Marine Science and Engineering, 2022)
Freight transport via ships is the cheapest and most effective way to transfer more than 80% of the global cargo volume. Seafarers have always been multinational, and accordingly, non-English-speaking crew members are becoming an increasing presence on board. Although marine engineers comprise half of the crews among all seafarers on board ships, Standard English guides, such as SMCP for navigation officers designed to reduce communication barriers, are unavailable for marine engineers. IMO conventions require marine engineers to possess adequate English skills. However, marine accidents due to inappropriate communication between crew members continue to occur. In this paper, 185 marine engineer cadets enrolled in two universities who had completed 12 months of training on a commercial ship or school training ship were surveyed in terms of the adequacy of English courses for marine engineers in class. This paper investigated whether the marine engineer English subjects are reviewed and analyzed and whether the English examination for the Certificate of Competence is suitable for the content taught in international maritime instruments and for the actual work of engineers. Finally, this paper aimed to establish a need to develop Standard English for engineers.